Association of coronary revascularisation after physician-referred non-invasive diagnostic imaging tests with outcomes in patients with suspected coronary artery disease: a post hoc subgroup analysis. Issue 9 (6th September 2020) - Kato, Takao; Uemura, Yukari; Naya, Masanao; Matsumoto, Naoya; Momose, Mitsuru; Hida, Satoshi; Yamauchi, Takao; Nakajima, Takatomo; Suzuki, Eriko; Inoko, Moriaki; Shiga, Tohru; Tamaki, Nagara
Abstract : Objective: We aimed to evaluate the association of the prognostic impact of coronary revascularisation with physician-referred non-invasive diagnostic imaging tests (single photon emission CT (SPECT) vs coronary CT angiography) for coronary artery disease. Design: A post hoc analysis of a subgroup from the patient cohort recruited for the Japanese Coronary-Angiography or Myocardial Imaging for Angina Pectoris Study. Setting: Multiple centres in Japan. Participants: From the data of 2780 patients with stable angina, enrolled prospectively between January 2006 and March 2008 in Japan, who had undergone physician-referred non-invasive imaging tests, 1205 patients with SPECT as an initial strategy and 625 with CT as an initial strategy were analysed. We assessed the effect of revascularisation (within 90 days) in each diagnostic imaging stratum and the interaction between the two strata. Primary and secondary outcome measures: Major adverse cardiac events (MACEs), including death, myocardial infarction, hospitalisation for heart failure and late revascularisation, were followed up for 1 year. The χ 2 test, Student's t-test, Kaplan-Meier analysis, log-rank test and multivariable Cox proportional hazard model were used in data analysis. Results: A total of 210 (17.4%) patients in the SPECT stratum and 149 (23.8%) in the CT stratum underwent revascularisation. Although in each stratum, the cumulative 1 year incidence of MACEs was significantly higher in patients who underwent revascularisation than in those who did not (SPECT stratum: 9.1 vs 1.2%, log-rank p<0.0001; CT stratum: 6.1 vs 0.8%, log-rank p=0.0001), there was no interaction between the risk of revascularisation and the imaging strata (SPECT stratum: adjusted HR (95% CI), 4.25 (1.86–9.72); CT stratum: 4.13 (1.16–14.73); interaction: p=0.97). Conclusion: The association of revascularisation with the outcomes of patients with suspected coronary artery disease was not different between SPECT-first and CT-first strategies in a physician-referred fashion.